Morphology and Anatomy of Macroalgae Community in Rap Rap Coastal Waters, Tongkaina Village, Manado City - Rafii, Keken Angliyana; Kepel, Rene Ch.; Kondoy, Khristin F I.; Mandagi, Stephanus V.; Tombokan, John L.; Lohoo, Anneke V. (Sam Ratulangi University, 2024)
Macroalgae are low-level plants that generally grow attached to certain substrates such as corals, mud, sand, rocks, and other hard objects. Macroalgae are algae that have a macroscopic body shape and size. A community is a group of beings living together in the same place. Thus the macroalgae community is a group of lower plants that have macroscopic body sizes living together. The coastal area of Rap-Rap Beach is located in Tongkaina Village, Manado City, North Sulawesi Province. This location is one of the stable macroalgae habitats, meaning that there is still little habitat damage that occurs, so macroalgae can still be obtained directly from nature. This coast is also known as mangrove ecotourism and the path to Bunaken Island. The purpose of this study is to describe the morphology and anatomy of each macroalgae species. Data collection using the Line Transect method with a squared sampling technique was carried out at the lowest low tide. Temperature measurement using a thermometer and salinity using a refractometer, and for determination of substrate visually see the type of substrate. Keywords: morphology, anatomy, community, macroalgae, Rap Rap. Abstrak Makroalga merupakan tumbuhan tingkat rendah yang umumnya tumbuh melekat pada substrat tertentu seperti pada karang, lumpur, pasir, batu dan benda keras lainnya. Makroalga yaitu alga yang memiliki bentuk dan ukuran tubuh makroskopik. Komunitas adalah kelompok makhluk yang hidup secara bersama-sama dalam suatu tempat yang bersamaan. Dengan demikian komunitas makroalga adalah kelompok tumbuhan rendah yang memiliki ukuran tubuh makroskopik yang hidup bersamaan. Wilayah pesisir Pantai Rap-Rap terletak di Kelurahan Tongkaina, Kota Manado, Provinsi Sulawesi Utara. Lokasi ini merupakan salah satu habitat makroalga yang stabil artinya masih sedikit kerusakan habitat yang terjadi, sehingga makroalga masih dapat diperoleh secara langsung dari alam. Pesisir ini juga dikenal sebagai ekowisata mangrove dan jalur ke Pulau Bunaken. Tujuan penelitian ini adalah mendeskripsikan morfologi dan anatomi masing-masing spesies makroalga. Pengambilan data menggunakan metode Line Transect dengan teknik sampling kuadrat yang dilakukan pada saat surut terendah. Pengukuran suhu menggunakan Thermometer dan salinitas menggunakan Refraktometer, dan untuk penentuan substrat dilihat secara visual jenis dari substrat tersebut. Kata kunci: morfologi, anatomi, komunitas, makroalga, Rap Rap.